Toward a Meta Understanding of Reality: The Problem of Reference in Russian Metarealist Poetry - Albena Lutzkanova-Vassileva (Studies in 20th & 21st Century Literature, 2005)
Through an in-depth analysis of Russian metarealist poetry, the paper seeks to undermine the increasingly popular belief in the self-referential nature of postmodern literature and deconstructive writing. To challenge the conviction that postmodern texts have cut off literary discourse from reality, the author focuses on the writing of Olga Sedakova and Elena Shvarts. Her analysis of Sedakova's Vrata, Okna, Arki attempts to draw a parallel between the schools of Russian symbolism and metarealism, and demonstrate the increased referential potential of metarealist writing. While symbolism juxtaposes the mundane reality here to the eternal spiritual world beyond, she argues in the paper, metarealism practices an optimistic monism, interconnecting perceptual realities to levels of existence in a metaphysical beyond. Introducing Gilles Deleuze and Félix Guattari's concept of the rhizome, the author analyzes the ways in which the poetry of Sedakova establishes connections with the multi-layered corpus of reality and thus expands the notion of referentiality. The paper proceeds with an examination of Shvarts's Lotsiia Nochi. The author advances a provocative reading of Shvarts's work from the point of view of Deleuze and Guattari's theory of de- and reterritorialization and Mikhail Epstein's notion of the metabole. By way of examining the metamorphic quality of metarealist poetry and the multifaceted modes of reality's manifestation within it, the essay discards as unwarranted the mourning over the postmodern eclipse of reality and the subject's incapacity to represent it. Metarealism, the author concludes, restores the pristine polyphony of our multidimensional universe and vindicates the prestige formerly allotted to referentiality.
Keywords: Russian metarealist poetry; Russian poetry; Poetry; Russia; postmodernism; postmodern literature; deconstructive; deconstruction; Olga Sedakova; Elena Shvarts; " Vrata; Okna; Arki" Russian symbolism; Russian metarealism; metarealist; metarealism; mundane; spiritual world; symbolism; monism; Gilles Deleuze; Félix Guattari; rhizome; referentiality; reality; Lotsiia Nochi; de-; reterritorialization; Mikhail Epstein; metabole; metarealist poetry